Tentative Identification of Critical Weather Factors to Circumvent Leaf Blast with Altered Dates of Sowing of Rice in the Foot-hills of Nagaland, India - Chetri, D. K.; Daiho, L.; Upadhyay, D. N. (International Journal of Bio-resource and Stress Management, 2011)
Studies on the effect of date of sowing and meteorological factors on the rice leaf blast severity caused by Pyricularia grisea (=P. oryzae Cav.,), showed that the crop sown between mid April and mid May recorded significantly less disease severity compared to postponed dates of sowing likely due to more rainfall and high relative humidity. Except for bright sunshine hours exhibiting significant negative correlation with disease severity (r = -0.521), all other weather factors under study showed positive correlation with the same. The prediction equation (Y=3.74+44.6x1+8.14x3– 15.29x4–2.58x6+7.9x7) derived through multiple regression analysis would be useful for forecasting disease severity and can be used as a component of integrated disease management programme for minimizing fungicidal spray.